(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article examines the role and significance of Ancient Egyptian art in the context of teaching the history of fine arts. Ancient Egyptian art, with its unique symbolism, stylized forms, and religious motifs, provides students with a foundational understanding of the evolution of visual expression and aesthetic principles. The study emphasizes how the analysis of tomb paintings, sculptures, and architectural monuments helps learners comprehend the cultural, spiritual, and social contexts that shaped artistic production in early civilizations. Furthermore, the article highlights pedagogical approaches for integrating Ancient Egyptian art into fine arts curricula, demonstrating its value in fostering analytical skills, visual literacy, and appreciation for historical artistic traditions. The research draws on comparative methods, historical documentation, and classroom practices to show how Ancient Egyptian art serves as a bridge connecting students to the broader narrative of world art history.